Evaluation of Sardinella lemuru Resource Status at the Nusantara Fisheries Port (NFP) Pengambengan - I Ketut Wija Negara; I Wayan Restu; Made Ayu Pratiwi; Diah Ayu Safitri; Andi Mannojengi; Bagus Sudananjaya; Made Ageng Astika; I Nyoman Sudiarsa (Institute for Research and Community Services Udayana University (LP2M Universitas Udayana), 2026)
The lemuru (Sardinella lemuru) fishery at Pengambengan Nusantara Fishing Port (NFP) is vital to the local economy but faces challenges from fluctuating catches, potentially linked to overexploitation. This study evaluates the sustainability status of this fishery using the Ecosystem Approach to Fisheries Management (EAFM) framework. Research conducted from May 2024 to July 2024 employed a mixed-methods approach, including direct observation, surveys, and interviews with 110 fishers, alongside biological data from 2,653 fish specimens. A multi-criteria analysis was used to calculate a composite sustainability index. The overall assessment yielded a score of 73,33 ('good' status), indicating that fisheries management at PNFP is generally satisfactory. However, critical issues were identified: a declining trend in fish size and inadequate management of Endangered, Threatened, and Protected (ETP) species. The study concludes that while the fishery is currently well-managed, urgent interventions are needed. Key recommendations include enforcing regulations on minimum catchable size and net mesh selectivity, alongside strengthening monitoring, control, and surveillance (MCS) to combat illegal, unreported, and unregulated (IUU) fishing and ensure long-term sustainability.